Scientific development and a new green deal - Xiaoxi Li (China Finance and Economic Review, 2014)
After 30 years of reform and opening, China has become the world's second largest economy. However, the fast growth has come at the high cost of environmental degradation and resource consumption. The existing resource reserves and environment will not able to sustain the rapid economic development of the future, which demands China to transform its model for development. China should keep pace with the trend of world civilization and grasp the opportunity for green development.
Keywords: 330; Resources and environment; Ecological civilization; Green development